Determinants of clinical outcomes of surgery for isolated severe tricuspid regurgitation. Issue 5 (2nd November 2020) - Park, Sung Jun; Oh, Jin Kyung; Kim, Seon-Ok; Lee, Seung-Ah; Kim, Ho Jin; Lee, Sahmin; Jung, Sung Ho; Song, Jong-Min; Choo, Suk Jung; Kang, Duk-Hyun; Chung, Cheol Hyun; Song, Jae-Kwan; et al.
Abstract : Objectives: Although the incidence of patients with isolated tricuspid regurgitation (TR) is increasing, data regarding the clinical outcomes of isolated TR surgery are limited. This study sought to investigate the prognostic implications according to procedural types, and to identify preoperative predictors of clinical outcomes after isolated TR surgery. Methods: Among consecutive 2610 patients receiving tricuspid valve (TV) procedure, we analysed 238 patients (age, 59.6 years; 143 females) who underwent stand-alone TV surgery (repair, 132; replacement, 106) for severe TR. Primary outcome was the composite of all-cause mortality and heart transplantation. Clinical outcomes between the repair and the replacement groups were compared after adjusting with the inverse probability of treatment weighting (IPTW) method. Results: During follow-up (median, 4.1 years), 53 patients died and 4 received heart transplantation. Multivariable analysis revealed that age (p=0.001), haemoglobin level (p=0.003), total bilirubin (p=0.040), TR jet area (p=0.005) and right atrial (RA) pressure (p=0.022) were independent predictors of the primary outcome. After IPTW adjustment, there were no significant intergroup differences in the risk of primary outcome (HR 1.01; 95% CI 0.55 to 1.87). In the subgroup analysis, tricuspid annular diameter was identified as a significant effect modifier (p=0.012) in the comparison between repair versus replacement, showing a trend favouring replacement in patients with annular diameter >44 mm. Conclusions: The outcomes of stand-alone severe TR surgery were independently associated with the severity of TR and RA pressure. In selected patients with severe annular dilation >44 mm, replacement may become a feasible option.